2013
DOI: 10.1002/phar.1231
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Counseling for Patients with Heart Failure or Myocardial Infarction: A Best Practices Model Developed by Members of the American College of Clinical Pharmacy's Cardiology Practice and Research Network Based on the Hospital to Home (H2H) Initiative

Abstract: Hospital to Home is a quality-based initiative led by the American College of Cardiology and the Institute for Healthcare Improvement, aimed at reducing 30-day hospital readmission rates for patients with heart failure or myocardial infarction. Several factors have been shown to attribute to early readmission for these conditions including comorbidities, environmental factors, insufficient discharge planning, lack of health literacy, and nonadherence to drug therapy. Pharmacists play a significant role in redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 95 publications
(154 reference statements)
0
31
0
Order By: Relevance
“…[1][2][3] Medication counselling opportunities are key times for pharmacists to speak to patients about their medications and the changes made to their therapies during their hospital stay. 2,[4][5][6][7] Failure by a hospital pharmacist to communicate effectively with patients may negatively impact a patient's ability to understand medication issues contributing to medication non-adherence. [8][9][10][11] The literature indicates patient benefits with hospital pharmacist involvement in discharge counselling and the practice has been incorporated into national pharmacy professional standards.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Medication counselling opportunities are key times for pharmacists to speak to patients about their medications and the changes made to their therapies during their hospital stay. 2,[4][5][6][7] Failure by a hospital pharmacist to communicate effectively with patients may negatively impact a patient's ability to understand medication issues contributing to medication non-adherence. [8][9][10][11] The literature indicates patient benefits with hospital pharmacist involvement in discharge counselling and the practice has been incorporated into national pharmacy professional standards.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Failure by a hospital pharmacist to communicate effectively with patients may negatively impact a patient's ability to understand medication issues contributing to poor health outcomes. [6][7][8][9] .…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Several studies have shown pharmacists to play significant roles in reducing medication-related readmissions by preventing adverse drug events. 12,17 In a report by Wiggins et al, pharmacist interventions in patients with heart failure demonstrated improved patient knowledge, reductions in medication discrepancies and errors, fewer hospital readmissions, and lower costs. 12 Although small in nature, this study demonstrates the potential for discharge counseling conducted by a pharmacist to reduce the number of hospital readmissions in the COPD population.…”
Section: Discussionmentioning
confidence: 99%